Operational and design aspects of accelerators for medical applications - Jacobus Maarten Schippers; Mike Seidel (Physical Review Special Topics. Accelerators and Beams, 2015)
Originally, the typical particle accelerators as well as their associated beam transport equipment were designed for particle and nuclear physics research and applications in isotope production. In the past few decades, such accelerators and related equipment have also been applied for medical use. This can be in the original physics laboratory environment, but for the past 20 years also in hospital-based or purely clinical environments for particle therapy. The most important specific requirements of accelerators for radiation therapy with protons or ions will be discussed. The focus will be on accelerator design, operational, and formal aspects. We will discuss the special requirements to reach a high reliability for patient treatments as well as an accurate delivery of the dose at the correct position in the patient using modern techniques like pencil beam scanning. It will be shown that the technical requirements, safety aspects, and required reliability of the accelerated beam differ substantially from those in a nuclear physics laboratory. It will be shown that this difference has significant implications on the safety and interlock systems. The operation of such a medical facility should be possible by nonaccelerator specialists at different operating sites (treatment rooms). The organization and role of the control and interlock systems can be considered as being the most crucially important issue, and therefore a special, dedicated design is absolutely necessary in a facility providing particle therapy.